2016
DOI: 10.14336/ad.2015.0929
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Histone Lysine Demethylases: Impact on the Aging Process and Age-Related Diseases

Abstract: Hypoxia is an environmental stress at high altitude and underground conditions but it is also present in many chronic age-related diseases, where blood flow into tissues is impaired. The oxygen-sensing system stimulates gene expression protecting tissues against hypoxic insults. Hypoxia stabilizes the expression of hypoxia-inducible transcription factor-1α (HIF-1α), which controls the expression of hundreds of survival genes related to e.g. enhanced energy metabolism and autophagy. Moreover, many stress-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 249 publications
(297 reference statements)
1
33
0
Order By: Relevance
“…This indicates a reduction of H3K27me3 methylation after inhibition of the mevalonate pathway in the analyzed cell lines. This confirms the possible association with starvation and autophagy, because similar observations were reported to be associated with hypoxia [ 52 ]. Quantitative reverse transcription real time polymerase chain reaction (RT-qPCR) confirmed the GeneChip data as shown in Figure 4 .…”
Section: Resultssupporting
confidence: 89%
“…This indicates a reduction of H3K27me3 methylation after inhibition of the mevalonate pathway in the analyzed cell lines. This confirms the possible association with starvation and autophagy, because similar observations were reported to be associated with hypoxia [ 52 ]. Quantitative reverse transcription real time polymerase chain reaction (RT-qPCR) confirmed the GeneChip data as shown in Figure 4 .…”
Section: Resultssupporting
confidence: 89%
“…The protein encoded by the KDM2B gene contains JmjC domain, CXXC motif, PHD domain, proline-rich region, and leucine-rich repeat. Among them, the JmjC domain is the active center that can catalyze the demethylation of H3K36me2 and H3K4me3 2831. Recently, some studies have suggested that KDM2B regulates gene expression in a JmjC-dependent manner and may be involved in tumorigenesis; thus, it has gradually received increasing research attention 25,32.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen deficiency is a master inducer of HIF accumulation but ROS and many other stress signals can also induce HIF accumulation even at normoxia, so called pseudohypoxia ( Salminen et al, 2016 ). ROS has been found to be a contributing factor in the stabilization of HIF-1α; ultimately allowing for HIF pathway activation in a number of studies ( Chandel et al, 1998 , 2000 ; Bell et al, 2007 ).…”
Section: Ros Induced Hif Accumulationmentioning
confidence: 99%